High-alloy wear-resistant roller repair welding material
By improving the cross-sectional design of flux cored welding wire and roll hole type, the service life of the surfacing materials caused by air holes and gas grooves in large-scale promotion and application of existing welding wires is solved, and efficient and stable surfacing effect is achieved, extending the service life is extended. .
Patent Information
- Application Number
- CN202311038982.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
AI Technical Summary
In the large-scale promotion and application of existing gas-protected flux cored welding wires, due to unstable production process, pores and gas grooves often appear in the welds, which affects the service life of the surfacing materials.
The improved cross-sectional design of flux cored wire is changed to a overlapping O-shaped cross-section, and the roll hole type is improved by combining strip edge and circumference bending method to form a overlapping O-shaped cross-section, reducing the external protective gas source Reliance improves welding efficiency and quality.
It realizes efficient surfacing, reduces the weight and structural complexity of the welding torch, improves wind and rust resistance, beautiful weld molding, strong process adaptability, and extends the service life of surfacing materials.
Smart Images

Figure CN119489293A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy repair welding, and in particular relates to a high-alloy wear-resistant roller repair welding material. Background Art
[0002] As the coal market becomes increasingly tight, the balance of supply and demand of power coal resources has been disrupted. It is becoming increasingly difficult for thermal power plants to purchase sufficient quantities of coal suitable for combustion, resulting in a large deviation of the quality of coal entering the furnace from the design value, which affects the safe and economic operation of thermal power plant units. The continuous change in coal quality not only affects the decline in boiler efficiency, but also leads to accelerated wear of pulverizing system equipment, increased maintenance costs, and the inability of wear-resistant parts to operate safely and stably after surfacing. In response to the above-mentioned serious problems, by upgrading the existing surfacing materials to super-anti-wear materials, high-wear-resistant surfacing materials can be achieved, especially under impact force. In addition to chromium carbides, surfacing materials also contain finely divided Zr and other refined products, which have stronger gain, higher response to impact loads, and a 10-15% longer life of anti-wear. They are more suitable for surfacing of materials such as rollers, chutes, grinding rollers, grinding discs, and roller presses.
[0003] As a new type of welding material, flux-cored welding wire is divided into two categories: gas-shielded flux-cored welding wire and self-shielded flux-cored welding wire. Gas-shielded flux-cored welding wire was first developed from solid wire gas shielded welding. Deoxidation and slag-forming components are added to the inside of the welding wire, and welding is performed under the protection of CO2, Ar or a mixture of the two gases. After years of development, this type of welding wire has been able to obtain high-strength, high-toughness, and beautifully formed welds. However, in the large-scale promotion and application of gas-shielded flux-cored welding wire, due to the unstable production process, pores and various forms of gas grooves and pressure pits will appear in the welds; such as: welding arc stability, welding spatter, slag removal, weld formation, all-position welding adaptability, weld quality and other phenomena, which will also affect the actual service life of the cladding material. Summary of the invention
[0004] The object of the present invention is to provide a high alloy wear-resistant roller repair welding method with large welding current, high deposition efficiency and improved actual service life of cladding materials.
[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0006] A high alloy wear-resistant roller repair welding material comprises the following steps:
[0007] 1) Formula of deposited metal for roller sleeve and lining of coal mill: composed of the following raw materials in parts by weight: 4.5-5.0% carbon, 26.0-28.0% chromium, 1.0-1.2% manganese, 0.3-0.5% silicon, ≤0.03% sulfur, ≤0.05% phosphorus, 0.5-1.0% vanadium, 1.0-1.5% niobium, 0.5-1.0% titanium, 2.0-3.0% tungsten, and the remainder iron;
[0008] 2) Alloy element transition coefficient formula: carbon 50-65%, chromium 85-95%, manganese 44-70%, silicon 50-75%, vanadium 75-85%, niobium 80-90%, titanium 20-25%, tungsten 90-95%;
[0009] 3) Preparation of wear-resistant cladding flux-cored wire:
[0010] ①The cross section of the flux-cored welding wire is improved from the original butt-jointed O-shaped cross section to an overlapping O-shaped cross section;
[0011] ② The hole type of the roller is improved by combining the strip edge and circumference combined bending method, changing the forming method of the steel strip on the wire rolling machine, and finally forming an overlapping O-shaped section.
[0012] According to the above characteristics, the prepared flux-cored welding wire and the original cladding welding wire were double-layered on a Q235 steel plate with a size of 200 mm × 500 mm × 20 mm.
[0013] In some examples, the welded test plates were wire cut, the sample size was 20 mm×20 mm×20 mm, the sample was ground with metallographic sandpaper, then polished, and then etched.
[0014] According to the above characteristics, the surfacing layer is high chromium cast iron, and the formula of the corrosive liquid is: 2.5g ferric chloride, 5g picric acid, 2ml hydrochloric acid, and 90ml distilled water.
[0015] In some examples, the roller sleeves or lining shoes are mounted on a positioner and compacted prior to cladding.
[0016] According to the above characteristics, the surfacing layer includes a surfacing base layer and a surfacing working layer. After the surfacing is completed, the grinding roller sleeve is hoisted out, placed on the sleepers, and naturally cooled in the room.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1) The present invention does not require an external protective gas source, reduces the weight of the welding gun, simplifies the structure, and is easier to operate; it has excellent wind resistance and can usually weld smoothly under a level 4 wind condition; it has low requirements on assembly dimensions; it has excellent rust resistance; it has reliable arc striking, good self-protection effect, stable arc burning, and beautiful weld formation; it has strong process adaptability.
[0019] 2) The self-shielded flux-cored welding wire of the present invention can be applied to various welding positions, and has good double-sided forming in single-sided welding; the production efficiency is high, and compared with manual welding, the allowable welding current of the self-shielded flux-cored welding wire is large and the deposition efficiency is high.
[0020] 3) The present invention adopts a variety of hole design methods including the combined bending method of the strip edge and the circumference to improve the hole design of the roller, change the forming method of the steel strip on the wire rolling machine, and finally form an overlapping O-shaped cross-section, thereby improving the quality of the flux-cored welding wire.
[0021] 4) The carbides in the welding wire cladding sample of the present invention are smaller, more numerous, and arranged more regularly. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the production line of the flux-cored welding wire rolling machine of the present invention.
[0023] Figure 2 It is a schematic diagram of the microstructure of the original welding wire surfacing sample of the present invention.
[0024] Figure 3 It is a schematic diagram of the energy spectrum test results of carbides in the original welding wire cladding sample of the present invention.
[0025] Figure 4 It is a schematic diagram of the energy spectrum analysis results of the solid solution phase in the original welding wire cladding sample of the present invention.
[0026] Figure 5 It is a schematic diagram of the microstructure of the wear-resistant welding material surfacing sample of the present invention.
[0027] Figure 6 It is a schematic diagram of the energy spectrum test results of carbides of the welding wire cladding sample of the present invention. DETAILED DESCRIPTION
[0028] Embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art. Those skilled in the art can obtain alternative technical solutions from the following description without departing from the spirit and scope of the present invention.
[0029] Example 1
[0030] A high alloy wear-resistant roller repair welding material comprises the following steps:
[0031] 1) Formula of deposited metal for roller sleeve and lining of coal mill: composed of the following raw materials in parts by weight: 4.5% carbon, 26.0% chromium, 1.0% manganese, 0.3% silicon, ≤0.03% sulfur, ≤0.05% phosphorus, 0.5% vanadium, 1.0% niobium, 0.5% titanium, 2.0% tungsten, and the balance iron;
[0032] 2) Alloy element transition coefficient formula: carbon 50%, chromium 85%, manganese 44%, silicon 50%, vanadium 75%, niobium 80%, titanium 20%, tungsten 90%;
[0033] 3) Preparation of wear-resistant cladding flux-cored wire:
[0034] ①The cross section of the flux-cored welding wire is improved from the original butt-jointed O-shaped cross section to an overlapping O-shaped cross section;
[0035] ② The hole type of the roller is improved by combining the strip edge and circumference combined bending method, changing the forming method of the steel strip on the wire rolling machine, and finally forming an overlapping O-shaped section.
[0036] The prepared flux-cored welding wire and the original surfacing welding wire are double-surfacing welded on a Q235 steel plate with a size of 200mm×500mm×20mm. The surfacing test plate is wire-cut, and the sample size is 20mm×20mm×20mm. The sample is ground with metallographic sandpaper, then polished, and then corroded. The surfacing layer is high-chromium cast iron, and the formula of the corrosive liquid is: 2.5g ferric chloride, 5g picric acid, 2ml hydrochloric acid, and 90ml distilled water. Install the grinding roller sleeve or lining tile on the positioner and press it before surfacing. The surfacing layer includes a surfacing base layer and a surfacing working layer. After the surfacing is completed, the grinding roller sleeve is hoisted out, placed on the sleepers, and naturally air-cooled indoors.
[0037] Example 2
[0038] A high alloy wear-resistant roller repair welding material comprises the following steps:
[0039] 1) Formula of deposited metal for roller sleeve and lining of coal mill: composed of the following raw materials in parts by weight: carbon 4.8%, chromium 27.0%, manganese 1.1%, silicon 0.4%, sulfur ≤0.03%, phosphorus ≤0.05%, vanadium 0.8%, niobium 1.2%, titanium 0.8%, tungsten 2.5%, iron balance;
[0040] 2) Alloy element transition coefficient formula: carbon 60%, chromium 90%, manganese 62%, silicon 65%, vanadium 80%, niobium 85%, titanium 22%, tungsten 92%;
[0041] The preparation of wear-resistant surfacing flux-cored welding wire is the same as that in Example 1.
[0042] Example 3
[0043] A high alloy wear-resistant roller repair welding material comprises the following steps:
[0044] 1) Formula of deposited metal for roller sleeve and lining of coal mill: composed of the following raw materials in parts by weight: 5.0% carbon, 28.0% chromium, 1.2% manganese, 0.5% silicon, ≤0.03% sulfur, ≤0.05% phosphorus, 1.0% vanadium, 1.5% niobium, 1.0% titanium, 3.0% tungsten, and the balance iron;
[0045] 2) Alloy element transition coefficient formula: carbon 65%, chromium 95%, manganese 70%, silicon 75%, vanadium 85%, niobium 90%, titanium 25%, tungsten 95%;
[0046] Powder is prepared according to the chemical composition of the deposited metal and the transition coefficient of the alloy elements, and the required amount of powder is calculated according to the following formula.
[0047]
[0048] Among them, M f E is the amount of alloy powder of a certain element added per 100 grams of powder; h is the mass fraction of an alloy element in the deposited metal; E d is the mass fraction of a certain alloy element in the steel strip; E q is the mass fraction of a certain alloy element in other alloy powders; D is the alloy element transition coefficient; k is the powder filling coefficient; h is the mass fraction of a certain alloy element in the alloy powder.
[0049] Through the analysis of the original welding wire surfacing samples, it was found that the original wear-resistant alloy system was also high-chromium cast iron, but the microstructure was coarse, the carbides were coarse in size, irregularly arranged and in small quantities. The reason for this was considered to be the lack of appropriate trace alloying elements. Therefore, when designing the formula of wear-resistant surfacing flux-cored welding wire, consider adding appropriate trace alloying elements. These elements include:
[0050] V: A strong carbide-forming element. VC formed by combining with C has a high melting point. It precipitates in the high-temperature melt in the form of solid particles in advance. As a nucleation core, it can significantly refine the grains, thereby increasing the strength of the material and the toughness.
[0051] Nb: A strong carbon and nitride forming element. A small amount of Nb can form fine nitrides or carbonitrides, refine the grains and increase the yield strength of the material.
[0052] Ti: A super carbon and nitride forming element. The formed carbides and nitrides are more stable.
[0053] W: A strong carbide-forming element. The WC generated by reacting with C has high hardness and good wear resistance, which can greatly improve the wear resistance of the material and also has a strong solid solution strengthening effect.
[0054] The preparation of wear-resistant surfacing flux-cored welding wire is the same as that in Example 1.
[0055] Wear-resistant surfacing flux-cored welding wire is prepared by coating the formulated powder with H08A steel strip, and the specification of the steel strip is 14mm. The powder filled in the flux-cored welding wire must be dried before adding, the particle size must be uniform and moderate, and the filling coefficient is strictly controlled between 49.5-50.5%. In order to solve the problem of loose powder packaging after the flux-cored welding wire is rolled and formed, the cross-section of the flux-cored welding wire is improved from the original butt-jointed O-shaped cross-section to an overlapping O-shaped cross-section. A variety of hole design methods, including the combined bending method of the strip edge and the circumference, are used to improve the hole shape of the roller, change the forming method of the steel strip on the wire rolling machine, and finally form an overlapping O-shaped cross-section to improve the quality of the flux-cored welding wire. The schematic diagram of the flux-cored welding wire production equipment is shown as follows Figure 1 shown.
[0056] The prepared flux-cored welding wire and the original surfacing welding wire were double-layer surfacing welded on a Q235 steel plate with a size of 200 mm × 500 mm × 20 mm. The surfacing process parameters are shown in Table 1.
[0057]
[0058] The welded test plate was wire cut to a size of 20mm×20mm×20mm for organization analysis. The sample was ground with metallographic sandpaper, then polished and then corroded. The base material was Q235 steel, and 4% nitric acid alcohol was used for corrosion; the welded layer was high chromium cast iron, and the formula of the corrosion solution was: 2.5g ferric chloride, 5g picric acid, 2ml hydrochloric acid, and 90ml distilled water.
[0059] The microstructure of the corroded samples was analyzed using a metallographic microscope, and the composition of the samples was analyzed using an energy dispersive spectrometer.
[0060] The microstructure of the original welding wire cladding sample is as follows Figure 2 As shown in Figure 1, the microstructure consists of white carbides and black solid solutions. The carbides are relatively coarse and irregularly arranged.
[0061] Figure 3 The following is the result of the energy spectrum test of carbides in the original welding wire cladding sample. It can be seen that the carbide has a high content of chromium and a high content of carbon. Since the atomic weight of carbon is very small, the quantitative result of the energy spectrum test is not accurate. However, from the content of chromium and carbon and the shape of the carbide, it can be judged that this carbide should be Cr7C3 or (Cr,Fe)7C3 type carbide.
[0062] Figure 4 The figure shows the energy spectrum analysis results of the solid solution phase in the original welding wire cladding sample. The solid solution contains a large amount of iron and a small amount of chromium, manganese, silicon, carbon and other elements, and is an iron-based solid solution.
[0063] The microstructure of the welding wire cladding sample of the present invention is as follows Figure 5The microstructure of the sample is also composed of white carbides and black solid solution. Different from the original welding wire cladding sample, the carbides in the welding wire cladding sample of the present invention are smaller, more neatly arranged, and more numerous.
[0064] The energy spectrum test results of the welding wire cladding sample of the present invention are as follows Figure 6 As shown. Figure 3 and Figure 6 It can be seen that the carbide phase composition in the welding wire cladding sample of the present invention is basically consistent with that in the original welding wire cladding sample, and can be determined to be the same type of carbide.
[0065] The microstructure of the welding wire cladding sample of the present invention is similar to that of the original welding wire cladding sample, both of which are composed of carbides and iron-based solid solutions. The carbides in the welding wire cladding sample of the present invention are finer, more numerous, and more regularly arranged.
[0066] The carbides in the microstructure of the welding wire cladding sample of the present invention and the original welding wire cladding sample should be Cr7C3 or (Cr, Fe)7C3 type carbides.
[0067] The hardness of the welding wire cladding sample of the present invention was tested by Rockwell hardness tester.
[0068] As shown in Table 2.
[0069]
[0070] The average hardness of the welding wire cladding sample of the present invention is HRC63.4.
[0071] The surfacing process of coal mill roller sleeve and lining is as follows:
[0072] 1. Installation
[0073] Install the roller sleeve or lining on the positioner and press it tightly before surfacing with moderate force. The lifting tools include lifting rings, wire ropes, etc., which must meet the lifting requirements to prevent breakage.
[0074] 2. Cleaning before welding
[0075] If there is rust on the part to be welded, use an angle grinder to clean it until the metallic luster is exposed; if there is oil or water on the part to be welded, burn it with an oxyacetylene flame until it is clean; if the ambient temperature is lower than 10°C, you can also use an oxyacetylene flame to heat the surface of the grinding roller to 50-60°C, and the heating should be as uniform as possible.
[0076] 3. Surfacing welding
[0077] Welding power supply: inverter DC power supply; polarity: DC reverse connection; current: 400~450A; voltage: 35~40V; welding line speed: 600~1000mm / min; cooling method: mist water cooling.
[0078] 4. Surfacing working layer
[0079] Welding power supply: inverter DC power supply; polarity: DC reverse connection; stem extension: 30-35mm; current: 400-600A; voltage: 35-40V; welding line speed: 600-1000mm / min; overlap: 3mm; cooling method: mist water cooling.
[0080] 5. Measurement
[0081] Use a special measuring fixture to measure the grinding roller sleeve. If the size is insufficient, continue with the surfacing.
[0082] 6. Post-weld treatment
[0083] After surfacing, the roller sleeve is hoisted out and placed on the sleepers for natural air cooling in the room. When the ambient temperature is too low, take appropriate insulation measures.
[0084] The above description is only a specific implementation mode of the present disclosure, but the protection scope of the embodiments of the present disclosure is not limited thereto. Any technician familiar with the technical field can easily think of changes, replacements or combinations within the technical scope disclosed in the embodiments of the present disclosure or under the ideas disclosed in the embodiments of the present disclosure, which should be included in the protection scope of the embodiments of the present disclosure.
Claims
1. A high alloy wear-resistant roller repair welding material, characterized in that The steps include: 1) Formula of deposited metal for roller sleeve and lining of coal mill: composed of the following raw materials in parts by weight: 4.5-5.0% carbon, 26.0-28.0% chromium, 1.0-1.2% manganese, 0.3-0.5% silicon, ≤0.03% sulfur, ≤0.05% phosphorus, 0.5-1.0% vanadium, 1.0-1.5% niobium, 0.5-1.0% titanium, 2.0-3.0% tungsten, and the remainder iron; 2) Alloy element transition coefficient formula: carbon 50-65%, chromium 85-95%, manganese 44-70%, silicon 50-75%, vanadium 75-85%, niobium 80-90%, titanium 20-25%, tungsten 90-95%; 3) Preparation of wear-resistant cladding flux-cored wire: ①The cross section of the flux-cored welding wire is improved from the original butt-jointed O-shaped cross section to an overlapping O-shaped cross section; ② The hole type of the roller is improved by combining the strip edge and circumference combined bending method, changing the forming method of the steel strip on the wire rolling machine, and finally forming an overlapping O-shaped section.
2. The high alloy wear-resistant roller repair welding material according to claim 1 is characterized in that The prepared flux-cored welding wire and the original cladding welding wire were double-clad on a Q235 steel plate with a size of 200 mm × 500 mm × 20 mm.
3. The high alloy wear-resistant roller repair welding material according to claim 2 is characterized in that The welded test plate was wire cut to a size of 20 mm × 20 mm × 20 mm. The sample was ground with metallographic sandpaper, polished, and then etched.
4. The high alloy wear-resistant roller repair welding material according to claim 3 is characterized in that The surfacing layer is high chromium cast iron, and the formula of the corrosive liquid is: 2.5g ferric chloride, 5g picric acid, 2ml hydrochloric acid, and 90ml distilled water.
5. The high alloy wear-resistant roller repair welding material according to claim 1, characterized in that Install the grinding roller sleeve or lining on the positioner and press it tightly before surfacing.
6. The high alloy wear-resistant roller repair welding material according to claim 2, characterized in that The surfacing layer includes a surfacing base layer and a surfacing working layer. After the surfacing is completed, the grinding roller sleeve is hoisted out and placed on the sleepers to be naturally air-cooled indoors.
Citation Information
Cited By
Grinding roller surface three-dimensional reconstruction and automatic repair welding system and control method thereof
CN120133785A
A three-dimensional reconstruction and automatic repair welding system for grinding roller surface and a control method thereof
CN120133785B